Surface circulation types and daily maximum and minimum temperatures in southern La Plata Basin - Penalba, Olga Clorinda (2013)
La Plata Basin is one of the most important agriculture and hydropower producing regions worldwide. Extreme climate events such as cold and heat waves and frost events have a significant socio-economic impact. This work analyzes the influence of the surface circulation in Southern South America on daily maximum (TMAX) and minimum (TMIN) temperatures in southern La Plata Basin. A Z test for the comparison of mean values and a Kolmogorov-Simirnov test for the comparison of distributions of TMAX and TMIN associated with each circulation pattern were performed. Specific daily surface circulation types are found to contribute to TMAX and TMIN anomalies and have a predominant occurrence in the development of the extreme temperature events in the region. The TMAX spatial response to the regional low level circulation is more homogenous and extended than the response of TMIN.